Enhancing efficiency of dye sensitized solar cells based on poly(propylene) carbonate polymer gel electrolytes incorporating double salts - Yee, Liaw Poh; Farhana, N.K.; Omar, Fatin Saiha; Sundararajan, V.; Bashir, Shahid; Saidi, Norshahirah Mohamad; Ramesh, Subramaniam; Ramesh, Kasi (Springer Verlag (Germany), 2020)
The performance of dye-sensitized solar cells (DSSCs) depends on the ionic conductivity and flexibility of electrolyte. Gel polymer electrolytes (GPEs) consisting poly(propylene) carbonate (PPC) incorporated with double salts (i.e. calcium iodide (CaI2) and tetrabutylammonium iodide (TBAI)) were prepared. X-ray diffraction (XRD) authenticated that the crystallinity of PPC is mitigated after incorporation of different concentrations of CaI2 and TBAI, which is favourable for ion transportation. Fourier-transform infrared spectroscopy (FTIR) unveils the occurrence of complexation between PPC and the double salts. GPE containing 10% of CaI2 and 30% of TBAI exhibits the highest ionic conductivity (1.838 mS cm−1) with the activation energy of 0.156 eV. The fabricated DSSC employing the optimized GPE exhibits the energy conversion efficiency (η) of 5.49%, short circuit current density (Jsc) of 16.6 mA cm−2, open circuit voltage (Voc) of 0.568 V and fill factor (FF) of 54%. © 2019, Springer-Verlag GmbH Germany, part of Springer Nature.